2021
DOI: 10.3389/fmicb.2021.628269
|View full text |Cite
|
Sign up to set email alerts
|

Burkholderiaceae Are Key Acetate Assimilators During Complete Denitrification in Acidic Cryoturbated Peat Circles of the Arctic Tundra

Abstract: Cryoturbated peat circles (pH 4) in the Eastern European Tundra harbor up to 2 mM pore water nitrate and emit the greenhouse gas N2O like heavily fertilized agricultural soils in temperate regions. The main process yielding N2O under oxygen limited conditions is denitrification, which is the sequential reduction of nitrate/nitrite to N2O and/or N2. N2O reduction to N2 is impaired by pH < 6 in classical model denitrifiers and many environments. Key microbes of peat circles are important but largely unkno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 100 publications
2
18
0
Order By: Relevance
“…Although the consumption of atmospheric N 2 O usually occurs in water-logged soils (Hallin et al 2018), this process has also been found in dry soils under oxic conditions (Wu et al 2013, Siljanen et al 2020), including high-arctic soils (Brummell et al 2014, Wagner et al 2019. Furthermore, the nosZ gene encoding the N 2 O reductase enzyme, which carries out N 2 O reduction to N 2 , has been detected in the surface layer of uplifted permafrost peatlands, similar to those studied here (Palmer andHorn 2012, Hetz andHorn 2021). Usually, N 2 O reduction occurs when the energetically more favorable electron acceptor NO 3 − is not available.…”
Section: Of Association With N 2 O Emissions and Importance Of The Wh...supporting
confidence: 77%
“…Although the consumption of atmospheric N 2 O usually occurs in water-logged soils (Hallin et al 2018), this process has also been found in dry soils under oxic conditions (Wu et al 2013, Siljanen et al 2020), including high-arctic soils (Brummell et al 2014, Wagner et al 2019. Furthermore, the nosZ gene encoding the N 2 O reductase enzyme, which carries out N 2 O reduction to N 2 , has been detected in the surface layer of uplifted permafrost peatlands, similar to those studied here (Palmer andHorn 2012, Hetz andHorn 2021). Usually, N 2 O reduction occurs when the energetically more favorable electron acceptor NO 3 − is not available.…”
Section: Of Association With N 2 O Emissions and Importance Of The Wh...supporting
confidence: 77%
“…4b). Other studies identified both taxa as widely present in heterotrophic denitrification systems [53][54][55] with certain members able to express complete denitrification pathways using myriad carbon sources. 54,56,57 Their combined increase in relative abundance as influent COD : NO 3 − -N approached the theoretical requirement for complete denitrification (5.9 : 1; see ESI †) coincided with increased fully-denitrifying performance (Fig.…”
Section: Microbial Ecologymentioning
confidence: 99%
“…Few, highly specialized taxa, mostly belonging to the family of Burkholderiaceae (co-occurring with Rhodanobacter sp. ), seem to be responsible for most of the denitrification occurring in these acidic soils using acetate as their energy source (Hetz & Horn, 2021). Despite the clear dominance of denitrification, the relative contribution of total 25 nitrification to the N2O emissions from the BP surfaces (~20%) was still significant and could be particularly important during drier summers (low soil water content) and at the end of the growing season when the N2O emissions are generally lower, as shown here and also in Gil et al (2017).…”
mentioning
confidence: 50%
“…This corroborates that moisture is a key N2O emission driver for the prevalence 30 of nitrification or denitrification to occur. Nitrifier denitrification can be, however, ruled out as a possible source of N2O in these soils since we know now that in Seida peat ammonia oxidizing archaea (AOA) are responsible for ammonia oxidation and ammonia oxidizing bacteria (AOB) are lacking there (Siljanen et al, 2019;Hetz & Horn, 2021). AOA are not capable for denitrification (anaerobic) in contrast to AOB.…”
mentioning
confidence: 99%